A comprehensive second law analysis of coil side air injection in the shell and coiled tube heat exchanger: An experimental study. (5th March 2019) - Khorasani, Saleh; Moosavi, Amin; Dadvand, Abdolrahman; Hashemian, Mehran
Highlights: Effect of air bubbles injection into the coil side of a horizontal SCT heat exchanger is studied. A new air bubbles injection method is proposed that does not need any change in the heat exchanger. Effect of air bubbles injection based on the second law of thermodynamics is analyzed. The performance of the heat exchanger was increased for certain values of the air flow rate. Abstract: Recently, the use of air injection into heat exchangers to increase their thermal performance has attracted great attention. In the present study, air is injected into the coil side of a horizontal shell and coiled tube heat exchanger. An external unit for air bubbles injection is used. By means of this method, there is no need to modify the original design of the heat exchanger. The effect of various air volume fractions (VF) on the number of thermal units (NTU) and pressure drop is examined. Besides, the effect of air bubbles injection is analyzed from the viewpoints of the second law of thermodynamics, which has not been performed previously. The entropy generation, augmentation entropy generation number and Witte-Shamsundar efficiency as important criteria are analyzed for the developed system. The results revealed that air bubbles injection into the coil side improved the thermal characteristics of the heat exchanger. Also it was observed that for achieving the best performance the volume fraction should be optimized. Besides, according to the second law analysis, it is realized that air bubbles injection into the coil side is more effective method for the heat exchangers with high liquid flow rates.